Development of a Territorial Planning Model of Wind and Photovoltaic Energy Plants for Self-Consumption as a Low Carbon Strategy - Francisco Santana-Sarmiento; Sergio Velázquez-Medina (Complexity)
Energy self-consumption is one of the strategies used for the optimization of renewable energy integration in electrical systems within a framework of sustainable energy policy development. Renewable energy self-consumption additionally contributes to the promotion of distributed generation. The aim of the present study is to develop a hybrid territorial planning model for the siting of areas suitable for the joint exploitation of wind and solar energy targeted principally at self-consumption. The methodology employed was based on the analytic hierarchy process (AHP) and geographical information systems (GIS), and the general area considered was the island of Gran Canaria (Spain). This island has an isolated electrical system. The case study involved locating areas close to populated settlements which are generally cut off from areas commonly marked out for large-scale wind and solar energy exploitation. The areas located with the model were differentiated according to the municipality they were in. The model that has been developed can be applied to any territory. The results obtained with the model can then be incorporated into territorial planning documents and/or national and regional and/or municipal files with the aim of optimizing the integration of renewable energy for self-consumption and advancing distributed electrical energy systems.